Real-Time 3D Face Alignment Using an Encoder-Decoder Network With an Efficient Deconvolution Layer - Ning, Xin; Duan, Pengfei; Li, Weijun; Zhang, Shaolin (IEEE signal processing letters, 2020)
In the field of 3D face alignment, most researchers have focused on improving the prediction accuracy of algorithms and ignored the portability for practical applications. To this end, this study presents a real-time 3D face-alignment method that uses an encoder-decoder network with an efficient deconvolution layer. The fusion of the encoding and decoding feature adds more abundant features to this network. An efficient deconvolution layer at the decoding stage applies the L1 norm to select useful features and generate abundant ones through linear operations. Experimental results using the standard AFLW2000-3D and AFLW-LFPA datasets show that our algorithm has low prediction errors with real-time applicability.